2009
DOI: 10.2746/042516408x330392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poll flexion and dynamic laryngeal collapse on tracheal pressure in Norwegian Coldblooded Trotter racehorses

Abstract: Induced poll flexion significantly affected peak inspiratory pressure (PIP) in all horses; however, PIPs were significantly more negative in those affected with DLC. Based upon the tracheal pressure measurements recorded in this study, DLC in NCTs is a severe obstructive upper respiratory tract disorder that is induced by poll flexion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
78
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(95 citation statements)
references
References 18 publications
(24 reference statements)
4
78
0
1
Order By: Relevance
“…Thus, the head and neck position in horses affects upper airway flow mechanics [2,9]. Decreasing the pharyngeal diameter leads to increased resistance in respiratory airflow.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the head and neck position in horses affects upper airway flow mechanics [2,9]. Decreasing the pharyngeal diameter leads to increased resistance in respiratory airflow.…”
Section: Discussionmentioning
confidence: 99%
“…Lane et al 4 reported that there were limitations in the evaluation of respiratory sounds by ear, and perception or interpretation of noises by the jockeys or trainers is not always reliable. In this study, too, some jockeys and trainers stated that an abnormal respiratory sound was heard from the horse controlled by the jockey until the last 600 m of the race, and that the abnormal respiratory sound disappeared when the horse stopped pulling and gained more speed during the last 600 m. This is interpreted by Strand et al 21 , who argued that the poll flexion by the jockey created pressure on the trachea and it caused mild and intermittent airway abnormalities resulting in dynamic upper respiratory tract disorders like dorsal pharyngeal collapse, bilateral aryepiglottic fold collapse, and bilateral vocal fold collapse. Strand et al 21 also reported that such problems were not seen when the horse's head was maintained in normal position.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, too, some jockeys and trainers stated that an abnormal respiratory sound was heard from the horse controlled by the jockey until the last 600 m of the race, and that the abnormal respiratory sound disappeared when the horse stopped pulling and gained more speed during the last 600 m. This is interpreted by Strand et al 21 , who argued that the poll flexion by the jockey created pressure on the trachea and it caused mild and intermittent airway abnormalities resulting in dynamic upper respiratory tract disorders like dorsal pharyngeal collapse, bilateral aryepiglottic fold collapse, and bilateral vocal fold collapse. Strand et al 21 also reported that such problems were not seen when the horse's head was maintained in normal position. This study demonstrates how effective the environmental factors (particularly the jockeys) are in the creation of dynamic upper respiratory tract dysfunctions that the horses are exposed to when running during exercise or on the racecourse.…”
Section: Discussionmentioning
confidence: 61%
“…The pathogenesis of this disorder is not fully understood. It is suspected that the underlying cause is not the distal axonopathy of the recurrent nerve but most likely a conformational change associated with poll flexion, when a more rostral position of the larynx occurs [25,26].…”
Section: Discussionmentioning
confidence: 99%